2020
DOI: 10.1080/10717544.2020.1837296
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive polymeric nanoparticles for biomedical application

Abstract: Nowadays, emerging radiolabeled nanosystems are revolutionizing medicine in terms of diagnostics, treatment, and theranostics. These radionuclides include polymeric nanoparticles (NPs), liposomal carriers, dendrimers, magnetic iron oxide NPs, silica NPs, carbon nanotubes, and inorganic metal-based nanoformulations. Between these nano-platforms, polymeric NPs have gained attention in the biomedical field due to their excellent properties, such as their surface to mass ratio, quantum properties, biodegradability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 167 publications
(236 reference statements)
0
24
0
Order By: Relevance
“…Hence, these findings are very promising. Radionuclide therapy has the advantage of delivering a concentrated dose to target tumor tissues, while preserving the surrounding healthy tissues, unlike the other current cancer therapies [ 19 , 39 , 67 , 71 , 72 ]. For the first time, the simultaneous ability of alpha and beta radiations to kill cancer cells has been demonstrated, using a low radioactive dose and obtaining high efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these findings are very promising. Radionuclide therapy has the advantage of delivering a concentrated dose to target tumor tissues, while preserving the surrounding healthy tissues, unlike the other current cancer therapies [ 19 , 39 , 67 , 71 , 72 ]. For the first time, the simultaneous ability of alpha and beta radiations to kill cancer cells has been demonstrated, using a low radioactive dose and obtaining high efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the need to modernize antitumor therapies has led to nanotechnology aiming to develop a more effective, safe, and efficient therapy. In this sense, radioactive nanoparticles have gained attention, due to their physical-chemical characteristics, biocompatibility, low toxicity, bioconjugation, and few side effects for healthy cells [ 67 , 68 , 69 ]. Although the literature states that alpha therapy is superior to beta therapy [ 1 ], there is a total absence of combined alpha and beta therapy for tumor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric NPs are a new type of nanomaterial that have attracted increasing attention in cancer diagnosis and treatment because they can be modified by chemotherapeutic drugs, antibodies, or nucleic acid ligands, and they can recognize cancer markers in cancer cell membranes or inside cells ( 43 ). They can be used to target the transport of drugs or nucleic acids during chemotherapy or gene therapy.…”
Section: Research Advances In Nanoplatforms For the Treatment Of Osmentioning
confidence: 99%
“…In addition, Jahangirian et al emphasised that nanoparticles within the range of 50–100 nm with a slightly negative charge can penetrate the membrane of cancer via systemic systems [ 46 ]. The study showed that 20 nm gold nanoparticles have been conjugated to different cellular targeting peptides and are able to penetrate biological membranes to the nucleus of targeted cancer [ 1 , 47 ].…”
Section: Gold Nanoparticles In Molecular Imagingmentioning
confidence: 99%